The effects of feeding a high concentrate ration containing 25% ground beef manure to fattening heifers in concrete and soil-surfaced lots - Drake, C.L.; Smart, L.I.; Smith, E.F.; Lipper, R.I. (Kansas State University. Agricultural Experiment Station, 2011)
This is a cooperative project with the Department of Agricultural Engineering to study surface runoff, in addition to animal performance. Twenty Hereford heifers were randomly allotted to four equal sized lots: 2 surfaced with concrete and 2 with soil. Self-feeders in soil-surfaced lots have concrete aprons.
Keywords: Beef; Ground beef; Concrete vs. soil-surfaced lots; High energy ration